(untitled) (INTERNATIONAL CONFERENCE ON INTERDISCIPLINARY SCIENCE, 2024)
This paper explores the various ways of addressing individuals in different cultures and languages, focusing on the use of idioms as a form of address. It examines the role of idioms in communication, their cultural significance, and the challenges they present to language learners. The study also investigates strategies for teaching idiomatic expressions and their integration into language teaching programs. Through a comparative analysis of idiomatic expressions in several languages, the paper highlights the diversity and complexity of addressing conventions and their impact on intercultural communication.